Glycemic Outcomes of Islet Autotransplantation - Al-Sofiani, Mohammed E.; Quartuccio, Michael; Hall, Erica; Kalyani, Rita Rastogi (Current diabetes reports, 2018)
Purpose of Review While there has been a growing utilization of total pancreatectomy with islet autotransplantation (TPIAT) for patients with medically refractory chronic pancreatitis over the past few decades, there remains a lack of consensus clinical guidelines to inform the counseling and management of patients undergoing TPIAT. In this article, we review the current clinical practice and published experience of several TPIAT centers, outline key aspects in managing patients undergoing TPIAT, and discuss the glycemic outcomes of this procedure. Recent Findings Aiming for lower inpatient glucose targets immediately after surgery (usually 100–120 mg/dl), maintaining all patients on subcutaneous insulin for at least 3 months to “rest” islets before an attempt is made to wean insulin, and close outpatient endocrinology follow-up after TPIAT particularly in the first year is common and related to better outcomes. Although TPIAT procedures and glycemic outcomes may differ across surgical centers, overall, approximately one third of patients are insulin independent at 1 year after TPIAT. Higher islet yield and lower preoperative glucose levels are among the strongest predictors of short-term post-operative insulin independence. Beyond 1 year post-operatively, the clinical management and long-term glycemic outcomes of patients after TPIAT are more variable. Summary A multidisciplinary approach is essential in optimizing the preoperative, inpatient, and post-operative management and counseling of patients about the expected glycemic outcomes after surgery. Consensus guidelines for the clinical management of diabetes after TPIAT and harmonization of data collection protocols among TPIAT centers are needed to address the current knowledge gaps in clinical care and research and to optimize glycemic outcomes after TPIAT.